2021
DOI: 10.3390/biomedicines9121790
|View full text |Cite
|
Sign up to set email alerts
|

Streptozotocin-Induced Diabetes in a Mouse Model (BALB/c) Is Not an Effective Model for Research on Transplantation Procedures in the Treatment of Type 1 Diabetes

Abstract: Type 1 diabetes (T1D) is characterized by the destruction of over 90% of the β-cells. C-peptide is a parameter for evaluating T1D. Streptozotocin (STZ) is a standard method of inducing diabetes in animals. Eight protocols describe the administration of STZ in mice; C-peptide levels are not taken into account. The aim of the study is to determine whether the STZ protocol for the induction of beta-cell mass destruction allows for the development of a stable in vivo mouse model for research into new transplant pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 78 publications
(134 reference statements)
0
10
0
Order By: Relevance
“…In the present study, we found that STZ-induced diabetes resulted in a significant increase in blood glucose, as mice developed severe hyperglycemia with concentrations reaching 400 mg/dL. Repeated administration of five low doses of STZ resulted in cellular and humoral immune reactions against β cells following subsequent infiltration of macrophages and lymphocytes, leading to β-cell lysis and type 1 diabetes ( 9 ). Despite the hyperglycemia, mice with STZ-induced diabetes did not become insulin-resistant.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In the present study, we found that STZ-induced diabetes resulted in a significant increase in blood glucose, as mice developed severe hyperglycemia with concentrations reaching 400 mg/dL. Repeated administration of five low doses of STZ resulted in cellular and humoral immune reactions against β cells following subsequent infiltration of macrophages and lymphocytes, leading to β-cell lysis and type 1 diabetes ( 9 ). Despite the hyperglycemia, mice with STZ-induced diabetes did not become insulin-resistant.…”
Section: Discussionmentioning
confidence: 58%
“…Therefore, we used streptozotocin (STZ)-induced diabetic mice. STZ is an antibiotic that promotes complete or partial destruction of pancreatic β cells and is commonly used experimentally to produce a type 1 diabetic animal model ( 9 ). We divided C57BL/6 mice into two groups, diabetic and non-diabetic, and we performed hematoxylin/eosin, picrosirius red, and Nissl staining.…”
Section: Introductionmentioning
confidence: 99%
“…Alloxan and STZ are the most popular diabetogenic chemicals in diabetes research. However, STZ has notable advantages over alloxan due to its rapid onset, the long half-life, low toxicity and cost-effectiveness ( Wszola et al, 2021 ). STZ is a toxic glucose analogue that is preferentially accumulated in the pancreatic β-cells via the GLUT2 glucose transporters in the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, GLUT2 transporters are not only expressed in pancreatic β-cells, but also in the epithelial cells of the kidneys and hepatocytes ( Sędzikowska and Szablewski, 2021 ; Yang et al, 2022 ). Thus, administration of STZ may result in nephro- and hepatotoxicity along with its potential to damage pancreatic β-cells ( Wszola et al, 2021 ). All six animal studies that investigated the effects of PS on diabetes used a single, high dose of STZ injection (up to 75 mg/kg) to induce pancreatic β-cells damage and diabetes in rats, which mimics type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, the dose of STZ is the key factor and a large injection dose will completely damage the islets. And absolute lack of insulin will result in type 1 diabetes (Wszola et al, 2021). Before STZ injection, rats and mice need to fast for 12 h without water, and males are used as much as possible because the response of females to STZ is not uniform, which may be related to estrogen levels.…”
Section: Construction Of Ir Animal Modelmentioning
confidence: 99%